EBV-positive diffuse large B-cell lymphoma of the elderly is an aggressive post-germinal center B-cell neoplasm characterized by prominent nuclear factor-kB activation - Montes-Moreno, Santiago; Odqvist, Lina; Diaz-Perez, Julio A; Lopez, Ana Batlle; de Villambrosía, Sonia Gonzalez; Mazorra, Francisco; Castillo, Maria E; Lopez, Mar; Pajares, Raquel; García, Juan F; Mollejo, Manuela; Camacho, Francisca I; et al. (Modern pathology, 2012)
Here, we report a retrospective series of 47 EBV-positive diffuse large B-cell lymphoma associated with advanced age. Histopathology allowed to the identification of different histological patterns: cases with polymorphic diffuse large B-cell lymphoma (29 cases), Hodgkin-like (8 cases) and polymorphic lymphoproliferative disorder-like (9 cases) patterns. One case was purely monomorphic diffuse large B-cell lymphoma. We show that this lymphoma type is a neoplasm with prominent classical and alternative nuclear factor-kB pathway activation in neoplastic cells (79% of the cases showed nuclear staining for p105/p50, 74% for p100/p52 and 63% for both proteins), with higher frequency than that observed in a control series of EBV-negative diffuse large B-cell lymphoma (χ2 <0.001). Most cases showed an activated phenotype (95% non-germinal center (Hans algorithm); 78% activated B cell (Choi algorithm)). Clonality testing demonstrated IgH and/or K/Kde/L monoclonal rearrangements in 64% of cases and clonal T-cell populations in 24% of cases. C-MYC (1 case), BCL6 (2 cases) or IgH (3 cases) translocations were detected by FISH in 18% cases. These tumors had a poor overall survival and progression-free survival (the estimated 2-year overall survival was 40±10% and the estimated 2-year progression-free survival was 36±9%). Thus, alternative therapies, based on the tumor biology, need to be tested in patients with EBV-positive diffuse large B-cell lymphoma of the elderly.